Where the world ended : re-unification and identity in the German borderland - Berdahl, Daphne, 1964-2007 (University of California Press, 1999)
Focusing on the re-unification of Germany, this text asks what happens when a political and economic system collapses overnight. It concentrates especially on how these changes have affected certain "border zones" of daily life - including social organization, gender and religion.